Analysis of information technology of decision-making support for health care problems - Мулеса, Оксана Юріївна (Eastern-European Journal of Enterprise Technologies, 2013)
Design and creation of information-analytical systems to meet the challenges of health care is an urgent problem nowadays. One of the directions of the state policy in the field of health care is the prevention and fight against HIV / AIDS. This policy provides a solution of several problems, including the problem of isolation of risk groups of HIV / AIDS from the general population, in particular the group of women who provide sexual services for a fee. The article proposes an approach to the design and creation of information-analytical system to assess the number of persons belonging to the risk groups. It defines the principles according to which the decision support system should be constructed. It was determined that its fundamental part should be a database, the design of which is carried out in accordance with the principle of openness. The components of the database system are static and dynamic data. The article also presents an overview of problems that arise in the process of designing of information-analytical system. In general, it describes the analytical set of problems of the system, i.e., a set of implementation of models and methods such as prior data preparation and actually problem solution